Isolation Of Potential Pathogenic Bacteria From Nasopharynx From Patients Having Cough For More Than Two Weeks. - Yesmin, Kazi; Shamsuzzaman, S M; Chowdhury, Akhtaruzzaman; Khatun, Khadeza; Alam, Jahangir (Bangladesh Journal of Medical Microbiology, 2012)
This cross sectional study was done from January 2009 to June 2010 in Microbiology department of Dhaka Medical College on isolation of potential pathogenic bacteria from nasopharynx from patients having cough for more than two weeks. The nasopharyngeal swabs were collected from 290 patients for culture and 101 blood samples were collected for slide agglutination test against anti- Bordetella antibody. In case of culture of nasopharyngeal swabs, 117 (73.12%) samples yielded growth of single organism, 16 (10%) yielded mixed growth and 27 (16.88%) samples yielded no growth in children. In adults, 85 (65.39%) samples yielded growth of single organism, 1 (0.77%) yielded mixed growth and 44 (33.84%) samples yielded no growth. Highest incidence (33.33%) of S. pneumoniae was found in age group of 1-5 years, highest incidence (32.20%) of N. meningitidis was found in age group of 18-25 years and highest incidence (32%) of Staph. aureus was found in age group of 25-50 years. One (0.63%) B. pertussis was isolated from a child and 5 (3.84%) B. parapertussis were isolated from adults. In this study, 116 (83.45%) samples yielded growth in lower socioeconomic group and 101 (70.62%) yielded growth in the samples of middle socioeconomic group. Among the study participants, 31(30.70%) were positive and 70 (69.30%) were negative for antibody against B. pertussis. In anti-Bordetella antibody positive cases, 14 (93.33%) children had duration of cough for 2-3 weeks, 7 (43.75%) adults had duration of cough for 3-4 weeks and 1 (6.25%) adults had more than 6 weeks. DOI: http://dx.doi.org/10.3329/bjmm.v4i2.10826